Espectroscopia no infravermelho próximo (NIRS) em unidade de terapia intensiva neonatal: experiência de um hospital universitário brasileiro - Luciana Oliveira Martins Pereira de Almeida; Gabriel Fernando Todeschi Variane1,2,3; Rafaela Fabri Rodrigues Pietrobom; Mauricio Magalhães; Daniela Pereira Rodrigues; Renato Gasperini; Alexandre Netto (Sociedade Brasileira de Pediatria, 2023)
Near-infrared spectroscopy (NIRS) is a non-invasive method to assess regional brain and/or renal oxygenation, and an important tool for a better clinical management. The aim of this study was to describe clinical cases of newborns admitted to the Neonatal Intensive Care Unit of a Brazilian university hospital who were monitored with NIRS, and to evaluate the applicability of NIRS demonstrating its use as a continuous monitoring method for newborns at high risk for brain injury. This study was part of the Conclusion Work of Medical Residency in Neonatology in Neonatology. Case 1: Persistent ductus arteriosus-NIRS guided indication for drug treatment. Case 2: Septic shock-NIRS was helpful identifying the need of inotropes. Case 3: Anemia of prematurity-NIRS showed an increase of cerebral oxygenation after red blood cells transfusions. Case 4: Hypoxic-ischemic encephalopathy-NIRS identified sign of poor neurological prognostic. NIRS is a continuous cerebral and renal perfusion monitoring method that has easy and good applicability and no complications. The cases reflect the importance and potential of NIRS in clinical practice and in helping diagnose for newborns, as well as enabling prognostic assessment. NIRS proved to be a method of good applicability, without short-term complications. Observing brain oxygenation values can help to avoid conditions associated with the development of neurological sequelae.